Application of the road traffic noise model to urban systems - WALERIAN, E.; JANCZUR, R.; CZECHOWICZ, M. (Archives of Acoustics, 1999)
In this paper, the computer simulation program PROP4, that allows prediction of the time-average sound level within an urban system, is presented together with the analysis of its accuracy. The simulation is based on an environmental noise model which contains the propagation model and the equivalent roadway model. The roadway as a noise source is represented by a sum of sound exposures due to the individual vehicle drive-by. The PROP4 allows for multi-lane roadways and different representations of sources for various classes of vehicles. Interactions of waves with obstacles are limited to multi-reflections from walls as well as single and double diffractions on wedges. The empirical data [14] have been compared with those obtained by using the PROP4 program. The comparison, especially for the relative decay of the time-average sound level with distance, shows a very good agreement with empirical data.